Perceptions of criteria for substandard and falsified medicines among doctors, pharmacists, and patients in DKI Jakarta: a mixed-methods study - Neneng Sri Purwaningsih; Yusi Anggriani; Hesty Utami Ramadaniat; Prih Sarnianto (Poltekkes Kemenkes Bandung, 2026)
Background: Indonesia continues to face challenges related to the circulation of substandard and counterfeit medicines. Perception plays an important role in shaping medicine-use behavior among healthcare professionals and patients. Objective: To identify factors associated with and dominant determinants of perceptions of substandard and counterfeit medicines among physicians, pharmacists, and patients in healthcare facilities in DKI Jakarta Province. Methods: A mixed-methods study with an explanatory design was conducted among 300 respondents, including 100 patients, 100 pharmacists, and 100 physicians. Quantitative samples were selected using cluster random sampling, while qualitative participants were recruited through purposive sampling. Data were collected through questionnaires and interviews and analyzed using chi-square tests and logistic regression (α<0.10). Results: The factors most strongly associated with perceptions of substandard medicines were knowledge among patients (95%), information among pharmacists (77%), and age among physicians (5%). For counterfeit medicines, the strongest associated factors were knowledge among patients (94%), gender among pharmacists (29%), and education among physicians (29%). Multivariate analysis showed that information was the dominant factor influencing perceptions of substandard medicines among patients (OR=2.000), pharmacists (OR=2.164), and physicians (OR=1.382). Perceptions of counterfeit medicines were predominantly influenced by knowledge, information, and education, respectively. Conclusion: Factors influencing perceptions of substandard and counterfeit medicines vary across respondent groups. Strengthening knowledge, education, and access to accurate information may improve awareness of substandard and counterfeit medicines.